#TITLE_ALTERNATIVE# - TRIANTORO (NIM: 22110020), AGUS
The potential of low rank coal reserves are abundant in Indonesia less than the optimal utilization of the background necessary to the development of low-rank coal gasification technology more effectively. Coal gasification is a process of converting coals into gasses is carbon monoxide (CO), hydrogen (H2), and methane (CH4) gasses with or without using a gasification agent such as air, O2, steam, CO2 or any combination of them in a gasification reactor. In the development of coal gasification there are some drawbacks, such as a large energy consuming, high reaction temperature, and difficult distillation of formed gas products. The purpose of this study is to investigate the influence of oxygen gasification agent, steam oxygen mixture and steam to the composition of the gas produced, examined the effect of temperature on the composition prosess gasification gas produced and compare gas products produced from low-rank coal gasification without the use of catalysts and gasification with using a nickel catalyst and K2CO3 as well as determine the effect of the addition of the catalyst on the gasification of the product gas produced In this study, an experiment of gasification on low ranking coals obtained from Aceh, Wara and PKN (Bulungan, East Kalimantan) was conducted by using a fluidized bed reactor. The variables in the gasification experiment were the sizes of coals, temperatures, and gasification agents. Grain size of coal used was -20 + 40 mesh. The temperatures used in this experiment were 6000C, 7000C, and 8000C. The gasification agents used were oxygen, oxygen-steam mixture, and steam. The coal gasification was carried out with and without Nickel and K2CO3 catalysts. The results showed that the composition of syngas with oxygen and steam-oxygen mixture gasification agents yielded higher CO concentration than H2. Conversely, for steam as the gasification agent, the composition of H2 was higher than of CO. In addition The use of nickel and K2CO3 catalyst could increase NHV value, cold gas efficiency, and carbon conversion value and decrease gasification temperature. The gasification with K2CO3 catalyst yielded higher NHV values than gasification without a catalyst or with nickel catalyst (12.107,34 kJ/Kg) by using PKN coal at 7000C with as oxygen steam mixture gasification agent. The same experiment variable, the efficiency of cold gas by using K2CO3 catalyst higher was compare to the value than with gasification without a catalyst or with a nickel catalyst (59,79%) occurring in PKN coal gasification at 7000C using a gasification agent of oxygen steam mixture. Additionally the carbon conversion was higher (62,97 %) by using a nickel catalyst, than without catalyst or with K2CO3 catalyst on PKN coal gasification at 6000C with as the oxygen gasification agent.